PEMETAAN GEOLOGI PADA PENAMPANG 140 UNTUK MENGETAHUI SEBARAN LITOLOGI, ALTERASI, MINERALISASI, DAN DENSITAS VEIN BESERTA HUBUNGANNYA DENGAN KEBERADAAN ZONA HIGH GRADE ORE PADA ENDAPAN PORFIRI BATU HIJAU PT. NEWMONT NUSA TENGGARA TENGGARA - Siti Nurul Qamarih (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
Mineral mining industry is much needed at the present time given themetal commodities is increasing from year to year. With increasing demands this,and the search for an evidentiary contained mineral reserves requires severalsteps in exploration activities in the early stages and update data. Batu Hijau is aporphyry copper-gold deposition (Cu-Au) with its formation is controlled by thedistribution of lithology, alteration processes, and vein density. The purpose of this study was to determine the distribution of lithology,alteration, mineralization, and vein density and its relationship with the presenceof high grade ore that is focused on section 140. The method used in this final study was conducted logging geologyconsisting of 14 drill holes, highwall mapping at a distance of ± 200 m, located onthe Northwest wall and across the Southeast section 140, and blasthole polygonmapping lies in the Northwest and Southeast the cross section 140. Based on drill hole logging, highwall mapping and blasthole mapping,lithology found growing at the study site consists of volcanic rock, equigranularquartz diorite rocks, tonalite intermediates rocks, and young tonalite rocks.Alteration consists of developing secondary biotite alteration (potassicalteration), partial biotite alteration (potassic alteration), pale green micaalteration (phyllic alteration), and chlorite-epidote alteration (propyliticalteration). Mineralization developed in the study site consists of bornite mineralcomposition largest copper 0.63% followed by 0.34% mineral chalcopyrite andpyrite minerals as mineral broadcaster.In the analysis stage is divided into themineralized zone, the dominant of mineral bornite (Bn> Cp> py), the dominant ofmineral chalcopyrite (Cp> Bn> py) and the dominant of mineral pyrite (Py> Cp>Bn). Vein density were found in the location of research classified as veindensity> 10%, vein density is 5% -10%, vein density is 3% -5%, and the density ofveins <3% with type vein vein consists of type A, type B vein, vein type C andmagnetite veins. The presence of high grade ore zone at section 140 contained inthe intermediate tonalite lithologies that are host rock mineralization along siderocks in contact with intermediate tonalite rocks on stage secondary biotite andpale green mica alteration, the dominant mineralization bornite and chalcopyrite,with vein density > 5%. Thus prioritized production targets on the physicalconditions.